Scalable GitOps Models for Multi-Cloud Infrastructure as Code Deployment - Deevi, Sri Ramya (International Journal of Computing and Engineering, 2022)
As enterprises embrace multi-cloud strategies to enhance agility, reduce vendor lock-in, and meet regulatory requirements, the need for scalable and reliable infrastructure management becomes critical. GitOps a paradigm that leverages Git as the single source of truth for declarative infrastructure offers a transformative approach to manage Infrastructure as Code (IaC) across heterogeneous cloud environments. This paper explores scalable GitOps models tailored for multi-cloud deployments, highlighting key architectural patterns, toolchains, and workflows that enable secure, auditable, and automated infrastructure operations. The study analyzes the strengths and limitations of leading GitOps tools such as ArgoCD and Flux in coordinating cross-cloud configurations and reconcile loops. The study also examines strategies for repository structuring, modularization of IaC, policy-as-code integration, and dynamic secrets management to support enterprise-scale deployments. The study propose a reference architecture that addresses the challenges of scalability, compliance, and resilience in multi-cloud GitOps workflows. My findings demonstrate that, when correctly implemented, GitOps can serve as a powerful operational model for achieving continuous delivery and governance in complex cloud-native ecosystems.